Prevalence of Undiagnosed ADHD: a Cross-sectional Study Among the Adult Population in Peshawar - Saaim Sikandar (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: ADHD is a lifelong neurodevelopmental disorder affecting academic, occupational, and social functioning. Often undiagnosed in adults, especially in Pakistan, it remains understudied among university students. This study explores the prevalence and functional impact of undiagnosed ADHD in Peshawar, aiming to inform screening, raise awareness, and guide local interventions Objectives: This study aimed to assess the prevalence of undiagnosed ADHD among undergraduate students and adults in Peshawar and to evaluate the associated functional impairments and socio-academic triggers. Methods: A cross-sectional study was conducted in urban Peshawar from February to June 2025. Ethics clearance (reference number: No 175/RC/NWSM/2024) to carry out the research was obtained from the host organization's Institutional Review Board (IRB) of Northwest School of Medicine prior to data collection. Verbal consent was obtained from participants, and anonymity was maintained in the process of data collection as well as data analysis. A total of 349 adults aged 20–40 years were recruited using convenience sampling. Participants completed a modified version of the WHO Adult Self-Report Scale (ASRS v1.1), which included an additional section assessing functional difficulties in daily life, social interaction, emotional regulation, and task performance. Data were analyzed using SPSS v25, with chi-square tests and descriptive statistics applied. Results: ADHD symptoms were highly prevalent, with 176 (50.4%) participants classified as borderline ADHD and 16 (4.6%) as moderate ADHD. Statistically significant associations were found between ADHD symptoms and educational level (χ² = 0.025) and occupation (χ² = 0.026), with medical professionals reporting higher symptom burden. Functional impairments were significantly more common in participants with borderline or moderate ADHD (p < 0.001), especially in emotional regulation (94.1% of the moderate ADHD group). No significant associations were found with gender or age. Conclusion: A substantial proportion of adults in Peshawar, especially within medical and academic communities, exhibit undiagnosed ADHD symptoms. These symptoms are associated with meaningful impairments in emotional and functional domains, highlighting the need for improved screening and support services. Culturally sensitive awareness and early intervention strategies are essential to address this neglected mental health burden. Keywords: Attention-deficit hyperactivity disorder, Functional Impairment, Medical Students